IgA deficiency: a risk factor for food allergy-related atopic dermatitis in infants and young children - Szczawińka-Popłonyk, Aleksandra; Komasińska, Paulina; Bręborowicz, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : The impaired immunosurveillance and dysfunctional antigen compartmentalization in primary immunodeficiencies may predispose affected children to allergic sensitization. Aim: The growing problem of allergic reactions to foods and the increase in non-IgE-mediated gastrointestinal disorders prompted us to investigate the impact of hypogammaglobulinemia on the prevalence and clinical phenotypes of food allergy. Material and methods: We performed a retrospective analysis of medical records of 78 infants and young children with deficiencies of one or more immunoglobulin isotypes and of 132 age-matched patients with normal immunoglobulin production in terms of prevalence and clinical manifestation of food allergy, atopic sensitization and physical development. Results : The symptoms of allergy to foods were demonstrated with a comparable frequency in children with hypogammaglobulinemia and with normal immunoglobulin levels (51% vs. 48%). The most prominent clinical phenotype of children with hypogammaglobulinemia was atopic dermatitis, whereas in children with normal immunoglobulin production, gastrointestinal symptomatology predominated. Uniquely, IgA deficiency showed a statistically significant (p < 0.05) correlation with food allergy and with cutaneous symptomatology. A striking predominance of non-IgE-mediated food allergy was demonstrated in both groups of the children studied, with elevated serum total IgE levels seen more commonly in children with normogammaglobulinemia than in those with hypogammaglobulinemia. Conclusions : The rate of non-IgE mediated allergic sensitization to foods in the population of infants and young children is high and clinically relevant. A selective IgA deficiency should alert physicians to assess affected children with respect to diverse phenotypes of food allergy.